Man or citizen : anger, forgiveness, and authenticity in Rousseau - Pagani, Karen, 1980- (The Pennsylvania State University Press, 2015)
"Examines the role of anger and forgiveness in the autobiographical, literary, and philosophical works of Jean-Jacques Rousseau. Argues that for Rousseau, anger is an inevitable outcome of social intercourse, and that forgiveness is central to his understanding of subjectivity and hence of moral and political action"--Provided by publisher